Pengukuran Sampel Magnetik Cair dengan Vibrating Sample Magnetometer (Vsm) - W Z Lubis; M Mujamilah (JPSE (Journal of Physical Science and Engineering), 2017)
This article discusses the performance of Vibrating Sample Magnetometer (VSM) Oxford 1.2 H in characterizing the magnetic samples in liquid form. Samples of water-based ferrofluid placed in a capillary tube pipe. Measurement of samples with varied position, volume and concentration as well as repeated measurements are carried out to evaluate the performance. From these series of measurements, it brings that optimal volume range with measurement results that can still be accounted for is 10 µl, with samples being in equilibrium position within the pick-up coil. The smallest sample concentration which still can be observed quantitatively is 0.332 mg/mL. Repeatability test gives the value of the magnetic moment deviation of ~ 4%. The accuracy of the sample preparation and positioning of the samples is analyzed being a major factor which causes this measurement error. In general it can be concluded that the liquid sample measurement will give better results when using reverse pipetting mode when putting the liquid samples within capillary tube using a micropipette. The measurement should be done as soon as possible after preparation.DOI: https://doi.org/10.17977/um024v2i22017p039